The influence of service quality and price on guest loyalty during the COVID-19 pandemic with guest satisfaction as an intervening variable at Hotel Grand Cityhall Medan - Ginting, Naomi Claudya Anantha; Sianturi, Marudut; Ariesa, Yeni (Priviet Social Sciences Journal, 2023)
The COVID-19 pandemic had a very significant impact on all aspects of the economy in Indonesia including tourism, as a result the number of foreign tourist visits to Indonesia decreased sharply and the ban on tourism activities caused the Indonesian tourism industry to experience a significant decline. To attract tourists to Indonesia, the world of tourism has improved a lot, one of which is hospitality. Hotel business actors must try to display different offerings and services by creating uniqueness and distinctiveness that can attract visitors to stay. This study aims to determine whether service quality and price affect customer loyalty through guest satisfaction at the Hotel Grand Cityhall Medan. The research method used is quantitative. The samples taken in this study were 98 respondents. This research is sourced from primary data obtained through questionnaires. The data analysis technique used in this study is Structural Equation Modeling (SEM) analysis using the Partial Least Square (PLS) program. The results in this study indicate that service quality and price have an influence on customer satisfaction, service quality has no influence on customer loyalty while price has an influence on customer loyalty, customer satisfaction has no influence on customer loyalty, service quality has no influence on customer loyalty through guest satisfaction and price has no influence on customer loyalty through guest satisfaction.